EFFECT OF GREEN COFFEE BEANS EXTRACT OINTMENTS FOR WOUND HEALING - Humaryanto, Humaryanto; Rahman, Ave Olivia (Jurnal Kedokteran Brawijaya, 2019)
Some interventions, such as coffee powder, are applied on wound to facilitate healing process. Coffee has several properties that can facilitate wound healing. Application of Robusta coffee bean ointment 22.5 % on full thickness wound could increase  fibroblast. Povidone iodine 10% has remained popular as wound antiseptic. This study aimed to evaluate the effect of green coffee bean extract in lower concentration for healing wound in rats. This study used male Sprague Dawley rats, 10 rats in each group. The skin incision was held in right back of rats with a diameter of 1.5 cm under lidocaine anesthetic subcutaneously. Group I was not given intervention, group II was given liquid povidone iodine 10%, and group III was given 15% green coffee bean extract in vaseline base. Interventions were held every day without wound debridement. Wound size was measured at day 0, 7 and 16.  Animals were sacrificed at day 7 (proliferative phase) and 16 (remodeling phase). Sections were stained using Haematoxilyn-eosin. Histopathology assessment of wound tissue is on reepithelization and presence of: inflammatory cells, fibroblast, collagen, and vascularization. Green coffee extract could  increase wound contraction  and  accelerated wound healing. Histopathology result on day 7 showed that green coffee extract had high response inflammatory cells and fibroblast. The provision of 15% green coffee bean extract ointment can accelerate wound healing  with higher inflammation response and fibroblast in proliferative phase .